Tax Compliance Perceptions and Formalization of Small Businesses in South Africa - Coolidge, Jacqueline; Ilic, Domagoj (2012)
This paper is based on large-scale surveys of formal and informal small businesses in South Africa, including questions about their experiences and perceptions about tax compliance, tax morale, and related variables. The survey findings suggest that formalization is more likely to take place in urban areas, involving relatively larger firms, and those who already use proper bookkeeping. Informal firms who said they were likely to register for tax in the near future were more likely than other informal firms to report higher satisfaction with government services, and to believe most businesses pay their taxes. The most-cited advantages of being registered for tax included better access to government services, better access to financing, and better opportunities for growth.